Physical activity and exercise for the prevention and management of mild cognitive impairment and dementia: a collaborative international guideline - Romero-Ortuno, Roman (My University, 2023)
Background: Physical activity and exercise have been suggested as effective interventions for the prevention and management of mild cognitive impairment (MCI) and dementia, but there are no international guidelines. Objectives: To create a set of evidence- and expert consensus-based prevention and management recommendations regarding physical activity (any bodily movement produced by skeletal muscles that results in energy expenditure) and exercise (a subset of physical activity that is planned, structured, repetitive), applicable to a range of individuals from healthy older adults to those with MCI/dementia. Methods: Guideline content was developed with input from several scientific and lay representatives' societies. A systematic search across multidisciplinary databases was carried out until October 2021. Recommendations for prevention and management were developed according to the GRADE and complemented by consensus statements from the expert panels. Recommendations: Physical activity may be considered for the primary prevention of dementia. In people with MCI there is continued uncertainty about the role of physical activity in slowing the conversion to dementia. Mind-body interventions have the greatest supporting evidence. In people with moderate dementia, exercise may be used for maintaining disability and cognition. All these recommendations were based on a very low/low certainty of evidence. Conclusions: Although the scientific evidence on the beneficial role of physical activity and exercise in preserving cognitive functions in subjects with normal cognition, MCI or dementia is inconclusive, this panel, composed of scientific societies and other stakeholders, recommends their implementation based on their beneficial effects on almost all facets of health.
PUBLISHED
Keywords: Cognition; Dementia; Exercise; Guidelines; Mild cognitive impairment; Older adult; Physical activity; Ageing; DEMENTIA; Age-related disability; Chronic Health Condition; Mental Health/Psychosocial disability; Health; Third age/ageing